Ophthalmosaurids (ichthyosauria: thunnosauria): alpha taxonomy, clades and names - Fernández, Marta Susana (2015)
Thunnosaurian ichthyosaurs represent the paradigm of reptilian body designed for a pelagic life style. Most derived thunnosaurian, the ophthalmosaurids, have been traditionally considered as members of a declining lineage. New findings and the re-examination of historical collections radically changed our conceptions about them. Opthalmosaurids were ecologically more diverse than previously thought. The past few decades have seen an increase of nominal species spurred by new findings and analyses. A still unresolved problem is that many species are only known by their holotypes. Nevertheless, morphological disparity is a compelling argument for considering them as valid. All recent cladistic analyses of ichthyosaurs recover ophthalmosaurids as a clade. Neither the addition of new information nor the addition of new entities resulted in its collapse. On this basis, the assignment of Linnaean rank to this clade (Ophtalmosauridae) is reasonable as it satisfied the primary recommended criteria for taxa naming: monophyly and stability. As the lists of species and genus names are used as input in major data bases for interpreting major turnover and/or extinction patterns, efforts must be focused on clarifying as much as possible the alpha taxonomy. Two major pending issues are the delimitation of Ophthalmosaurus-Baptanodon, and Platypterygius. The case of Platypterygius is complex because the type species is poorly known, its holotype is lost, and there is no consensus among specialist about the species that should be included in this genus. On the other hand, we advocate for the use of the name Baptanodon natans instead of Ophthalmosaurus natans.